Vitamin E ameliorates the decremental effect of paraquat on cardiomyocyte contractility in rats. - Mohamed Abdelmonem Fahim; Frank Christopher Howarth; Abderrahim Nemmar; Mohamed Anwar Qureshi; Mohamed Shafiullah; Petrilla Jayaprakash; Mohamed Yousif Hasan (PLoS ONE, 2013)
BACKGROUND: Exposure to pesticides and industrial toxins are implicated in cardiovascular disease. Paraquat (PAR) is a toxic chemical widely used as an herbicide in developing countries and described as a major suicide agent. The hypothesis tested here is that PAR induced myocardial dysfunction may be attributed to altered mechanisms of Ca(2+) transport which are in turn possibly linked to oxidative stress. The mechanisms of PAR induced myocardial dysfunction and the impact of antioxidant protection was investigated in rat ventricular myocytes. METHODOLOGY: Forty adult male Wistar rats were divided into 4 groups receiving the following daily intraperitoneal injections for 3 weeks: Group 1 PAR (10 mg/kg), Control Group 2 saline, Group 3 vitamin E (100 mg/kg) and Group 4 PAR (10 mg/kg) and vitamin E (100 mg/kg). Ventricular action potentials were measured in isolated perfused heart, shortening and intracellular Ca(2+) in electrically stimulated ventricular myocytes by video edge detection and fluorescence photometry techniques, and superoxide dismutase (SOD) and catalase (CAT) levels in heart tissue. PRINCIPAL FINDINGS: Spontaneous heart rate, resting cell length, time to peak (TPK) and time to half (THALF) relaxation of myocyte shortening were unaltered. Amplitude of shortening was significantly reduced in PAR treated rats (4.99±0.26%) and was normalized by vitamin E (7.46±0.44%) compared to controls (7.87±0.52%). PAR significantly increased myocytes resting intracellular Ca(2+) whilst TPK and THALF decay and amplitude of the Ca(2+) transient were unaltered. The fura-2-cell length trajectory during the relaxation of the twitch contraction was significantly altered in myocytes from PAR treated rats compared to controls suggesting altered myofilament sensitivity to Ca(2+) as it was normalized by vitamin E treatment. A significant increase in SOD and CAT activities was observed in both PAR and vitamin E plus PAR groups. CONCLUSIONS: PAR exposure compromised rats heart function and ameliorated by vitamin E treatment.